Manajemen Kurikulum Pendidikan Pesantren Salaf: Studi PP. Baitus Sholihin Zainul Hasan Genggong Probolinggo - Nanang Qosim (At- Ta'lim : Jurnal Pendidikan, 2019)
Management of the Salaf boarding school curriculum (Study of PP. Bitus Sholihin Genggong Probolinggo). The study was motivated by the many educational curricula today based on (global) market needs. While the Islamic Boarding School Salaf PP. Baitus Sholihin Genggong still maintains Islamic-based education while maintaining its salaf model. Even so, students graduated from the Islamic Boarding School Salaf PP. Baitus Sholihin Genggong were able to face the challenges of the times in the era of modernization. Keyword : Management, Salaf boarding school, and curriculum